How does the human rights perspective help to shape the food and nutrition policy research agenda? - Haddad, Lawrence James; Oshaug, Arne (International Food Policy Research Institute, 1999)
Food as a human right was first laid down 50 years ago in the Universal Declaration of Human Rights. The last 10 years, in particular, have witnessed an increased recognition of the importance of the human rights approach for designing policies and interventions that promote food and nutrition security, as evidenced by the highly visible role given to human rights at the 1996 World Food Summit. But, given that the design of effective policies and interventions is based on good analysis and information, what are the implications of the human rights approach for the food and nutrition policy research agenda? This is the question we address in this paper. We note several implications of the human rights perspective in terms of (1) new research areas, (2) new perspectives on old issues, and (3) implications for research methods.